Use of multilayer silicone foam dressings as adjuvant therapy to prevent pressure injuries. (2nd September 2021) - Faucher, Nathalie; Barateau, Martine; Hentz, Franck; Michel, Philippe; Meaume, Sylvie; Rousseaux, Chantal; Marty, Marc; Fort, Marc le; Nicolas, Benoit
Abstract : Despite progress in the prevention of pressure injuries (PIs), they remain a challenging public health problem because of their frequency and morbidity. Protection of the skin by multilayer silicone foam dressings may be an adjuvant measure to prevent PIs in high-risk patients. Despite the available clinical data and published recommendations on this measure, caregivers face difficulties in identifying patients who would benefit from this adjuvant measure. The objective of this work was to define the profiles of high-risk patients who would benefit optimally from this measure in combination with basic preventive procedures. This consensual expert opinion was drawn up using two methods: the Nominal Group Technique with eight medical and paramedical experts, and the Delphi process with 16 experts. The bases for this expert consensual opinion were a formal search and analysis of the published literature regarding evidence on the prevention of PIs using multilayer silicone foam dressings. The consensual expert opinion reported here addresses five proposals mostly intended to define patients who would benefit from the use of a multilayer silicone foam dressing (≥4 layers) to prevent PIs (sacrum and heels).